Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s1519-69842006000300023
|View full text |Cite
|
Sign up to set email alerts
|

First record of Cephalobaena tetrapoda (Pentastomida: Cephalobaenidae) as a parasite on Liophis lineatus (Ophidia: Colubridae) in Northeast Brazil

Abstract: Cephalobaenidae constitutes one of the main pentastomid groups infecting the respiratory tract of snakes. Six specimens of Liophis lineatus, a colubrid, were collected by active capture and pitfalls installed on the banks of the Batateiras river, close to its source, in the 'APA -Área de Proteção Ambiental' (a protected environmental area of the 'IBAMA -Brazilian Institute for the Environment and Natural Resources'), and in a remnant of the humid tropical forest 'FLONA -Floresta Nacional do Araripe', both in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 9 publications
2
21
0
2
Order By: Relevance
“…Almeida et al (2008b) stated that together with morphological evidence, such evaluation would reinforce the proposition for the existence of a new species. However, data obtained by Almeida et al (2006a;2008a;2008b) indicates that two species of pentastomids, Cephalobaena tetrapoda Heymons, 1922 and Raillietiella furcocerca, should be generalists because of their recorded variety of hosts. Anjos et al (2008) reported only one female of gecko, H. mabouia, parasitized by R. mottae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almeida et al (2008b) stated that together with morphological evidence, such evaluation would reinforce the proposition for the existence of a new species. However, data obtained by Almeida et al (2006a;2008a;2008b) indicates that two species of pentastomids, Cephalobaena tetrapoda Heymons, 1922 and Raillietiella furcocerca, should be generalists because of their recorded variety of hosts. Anjos et al (2008) reported only one female of gecko, H. mabouia, parasitized by R. mottae.…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications have included evaluations on infection rates, prevalence, and mean intensity of infection in studies of snakes, amphisbaenians and lizards of the northeastern region of Brazil (Dias et al, 2005;Almeida et al, 2006a;Almeida et al 2006b;Almeida et al 2007;Almeida et al 2008a;Almeida et al 2008b;Anjos et al, 2008), nevertheless, only four lizard species were investigated. Dias et al (2005) reported a likely new species of Raillietiella aff.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, results from Martínez et al (2000) were obtained from collections in a different area and specimens were sampled from several localities across the northeastern region of Argentina. Therefore, the results presented in this study and by Almeida et al (2006) represent the only ecological information available on pentastomid parasitism in snakes for Northeastern Brazil, which highlights the need for further investigations in different ecosystems in order to find patterns of prevalence and intensity of infection for ophidians in South America.…”
Section: Host Species (N)mentioning
confidence: 85%
“…During the identification of individuals, we also compared the specimens with material from the Helminthological Collection of the Oswaldo Cruz Institute (CHIOC) for confirmation of identity: Cephalobaena tetrapoda (29185a-d, 29190a-l), Raillietiella freitasi (Motta and Gomes, 1968) generalist parasites as they have been reported as parasitizing snakes belonging to several genera and families of snakes, which in turn present distinct diets, ranging from arthropods to vertebrates (Sambon, 1922b;Heymons, 1935;Motta, 1963a, b;Rego, 1981Rego, , 1983Rego, , 1984Almeida and Christoffersen, 2002;Almeida et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation